Bio-tea prevents membrane destabilization during Isoproterenol-induced myocardial injury. Issue 3 (September 2017) - Lobo, Reema Orison; Chandrasekhar Sagar, B.K.; Shenoy, Chandrakala K.
Abstract: The present study was undertaken to determine the membrane-stabilizing effect of Bio-tea in the prevention of myocardial injury caused by isoproterenol in rats. The efficiency of Bio-tea pretreatment was compared against black tea pretreatment and the positive control (rats with isoproterenol-induced myocardial infarction) and negative control (normal control rats). For this purpose, biochemical analysis of the in vivo antioxidants (superoxide dismutase, catalase, and reduced glutathione), glycoprotein components (hexose, hexosamine, sialic acid, and fucose), lipids (total, ester and free cholesterol, triglycerides, free fatty acids, and phospholipids), and transmembrane protein activities (Na + /K + ATPase, Ca 2+ ATPase, and Mg 2+ ATPase) was carried out along with the histological and ultrastructural study of the myocardial tissue. Induction of myocardial infarction using isoproterenol resulted in a significant decrease in tissue antioxidants and an increase in the levels of total, ester and free cholesterol, triglycerides, free fatty acids, and glycoprotein components in plasma and heart. The phospholipid content showed an increase in plasma and a simultaneous decrease in the heart tissue, while the Na + /K + ATPase activity decreased and Ca 2+ ATPase and Mg 2+ ATPase activities increased, resulting in destabilization of the membranes. Pretreatment with Bio-tea was able to bring these components to near normal, indicating its reactive-oxygen-species-scavenging, lipid-lowering, membrane-stabilizing and glycoprotein-modulating effects and lending credibility to the regular use of Bio-tea.